Chromatic Fulleropyrrolidine as Long‐Lived Metal‐Free Catalyst for CO2 Photoreduction Reaction - Wang, Shih‐Hao; Raja, Rathinam; Hsiow, Chuen‐Yo; Khurshid, Farheen; Yang, Hau‐Ren; Chung, Po‐Wen; Lai, Yu‐Ying; Jeng, Ru‐Jong; Wang, Leeyih (ChemSusChem, 2022)
Conversion of CO2 into carbonaceous fuels with the aid of solar energy has been an important research subject for decades. Owing to their excellent electron‐accepting capacities, fullerene derivatives have been extensively used as n‐type semiconductors. This work reports that the fulleropyrrolidine functionalized with 4,7‐di(thiophen‐2‐yl)benzo[c][1,2,5]thiadiazole, abbreviated as DTBT‐C60, could efficiently catalyze the photoreduction of CO2 to CO. The novel C60‐chromophore dyad structure facilitated better usage of solar light and effective dissociation of excitons. Consequently, the DTBT‐C60 exhibited a promising CO yield of 144 μmol gcat−1 under AM1.5G solar illumination for 24 h. Moreover, the isotope experiments demonstrated that water molecules could function as an electron source to reactivate DTBT‐C60. Impressively, DTBT‐C60 exhibited an extremely durable catalytic activity for more than one week, facilitating the practical application of photochemical CO2 reaction. Molecular photocatalyst: C60‐chromophore dyad effectively catalyzes the photoreduction reaction of CO2 to produce CO with 100 % selectivity by directly using water molecules as a source of electrons to regenerate chromophore units. The dyad structure markedly enhances the dissociation efficiency of excitons and reduces the recombination rate of charge carriers. This molecular catalyst exhibits a steady catalytic activity during a 7‐day photoreaction.